Comprehensive device simulation of 23.36% efficient two-terminal perovskite-PbS CQD tandem solar cell for low-cost applications - Jaya Madan (Nature Portfolio, 2021)
Abstract The major losses that limit the efficiency of a single-junction solar cell are thermalization loss and transmission loss. Thus, to efficiently utilize the full solar spectrum and to mitigate these losses, tandem solar cells (TSC) have significantly impacted the photovoltaic (PV) landscape. In this context, the research on perovskite/silicon tandems is currently dominating the research community. The stability improvements of perovskite materials and mature fabrication techniques of silicon have underpinned the rapid progress of perovskite/silicon TSC. However, the low absorption coefficient and high module cost of the silicon are the tailbacks for the mass production of perovskite/silicon TSCs. Therefore, PV technology demands to explore some new materials other than Si to be used as absorber layer in the bottom cell. Thus, here in this work, to mitigate the aforementioned losses and to reduce cost, a 23.36% efficient two-terminal perovskite-PbS CQD monolithic tandem solar cell has been designed through comprehensive device simulations. Before analyzing the performance of the proposed TSC, the performance of perovskite top cells has been optimized in terms of variation in optical properties, thickness, and interface defect density under standalone conditions. Thereafter, filtered spectrum and associated integrated filtered power by the top cell at different perovskite thickness from 50 to 500 nm is obtained to conceive the presence of the top cell above the bottom cell with different perovskite thickness. The current matching by concurrently varying the thickness of both the top and bottom subcell has also been done to obtain the maximum deliverable tandem JSC for the device under consideration. The top/bottom subcell with current matched JSC of 16.68 mA cm−2/16.62 mA cm−2 showed the conversion efficiency of 14.60%/9.07% under tandem configuration with an optimized thickness of 143 nm/470 nm, where the top cell is simulated under AM1.5G spectrum, and bottom cell is exposed to the spectrum filtered by 143 nm thick top cell. Further, the voltages at equal current points are added together to generate tandem J–V characteristics. This work concludes a 23.36% efficient perovskite-PbS CQD tandem design with 1.79 V (VOC), 16.67 mA cm−2 (JSC) and 78.3% (FF). The perovskite-PbS CQD tandem device proposed in this work may pave the way for the development of high-efficiency tandem solar cells for low-cost applications.